Estimating the risk of adverse birth outcomes in pregnant women undergoing non-obstetric surgery using routinely collected NHS data: an observational study - Paul Aylin; Phillip Bennett; Alex Bottle; Stephen Brett; Vinnie Sodhi; Angus Rivers; Violeta Balinskaite (National Institute for Health Research, 2016)
Background: Previous research suggests that non-obstetric surgery is carried out in 1-2% of all pregnancies. However, there is limited evidence quantifying the associated risks. Furthermore, of the evidence available, none relates directly to outcomes in the UK, and there are no current NHS guidelines regarding non-obstetric surgery in pregnant women. Objectives: To estimate the risk of adverse birth outcomes of pregnancies in which non-obstetric surgery was or was not carried out. To further analyse common procedure groups. Data Source: Hospital Episode Statistics (HES) maternity data collected between 2002-3 and 2011-12. Main outcomes: Spontaneous abortion, preterm delivery, maternal death, caesarean delivery, long inpatient stay, stillbirth and low birthweight. Methods: We utilised HES, an administrative database that includes records of all patient admissions and day cases in all English NHS hospitals. We analysed HES maternity data collected between 2002-3 and 2011-12, and identified pregnancies in which non-obstetric surgery was carried out. We used logistic regression models to determine the adjusted relative risk and attributable risk of non-obstetric surgical procedures for adverse birth outcomes and the number needed to harm. Results: We identified 6,486,280 pregnancies, in 47,628 of which non-obstetric surgery was carried out. In comparison with pregnancies in which surgery was not carried out, we found that non-obstetric surgery was associated with a higher risk of adverse birth outcomes, although the attributable risk was generally low. We estimated that for every 287 pregnancies in which a surgical operation was carried out there was one additional stillbirth; for every 31 operations there was one additional preterm delivery; for every 25 operations there was one additional caesarean section; for every 50 operations there was one additional long inpatient stay; and for every 39 operations there was one additional low-birthweight baby. Limitations: We have no means of disentangling the effect of the surgery from the effect of the underlying condition itself. Many spontaneous abortions will not be associated with a hospital admission and, therefore, will not be included in our analysis. A spontaneous abortion may be more likely to be reported if it occurs during the same hospital admission as the procedure, and this could account for the associated increased risk with surgery during pregnancy. There are missing values of key data items to determine parity, gestational age, birthweight and stillbirth. Conclusions: This is the first study to report the risk of adverse birth outcomes following non-obstetric surgery during pregnancy across NHS hospitals in England. We have no means of disentangling the effect of the surgery from the effect of the underlying condition itself. Our observational study can never attribute a causal relationship between surgery and adverse birth outcomes, and we were unable to determine the risk of not undergoing surgery where surgery was clinically indicated. We have some reservations over associations of risk factors with spontaneous abortion because of potential ascertainment bias. However, we believe that our findings and, in particular, the numbers needed to harm improve on previous research, utilise a more recent and larger data set based on UK practices, and are useful reference points for any discussion of risk with prospective patients. The risk of adverse birth outcomes in pregnant women undergoing non-obstetric surgery is relatively low, confirming that surgical procedures during pregnancy are generally safe. Future work: Further evaluation of the association of non-obstetric surgery and spontaneous abortion. Evaluation of the impact of non-obstetric surgery on the newborn (e.g. neonatal intensive care unit admission, prolonged length of neonatal stay, neonatal death). Funding: The National Institute for Health Research Health Services and Delivery Research programme.